The Role of the Tax System in the Diversification of the Land Fund - Mahsudov Muhammadbek Dilshodbek ugli (Research Parks Publishing LLC, 2021)
In the world practice, considerable experience has been accumulated in regulating the use of land resources as an important factor and tool that determines socio-economic progress, a specific component of property, an object of taxation, rent and other financial relations. The article develops proposals for achieving high efficiency in the use of land resources by simplifying the taxation mechanism.